THE INFLUENCE OF TALKING STICK LEARNING MODEL TO STUDENT LEARNING RESULTS IN BASIC TECHNOLOGY LESSONS OF BASIC AUTOMOTIVE TECHNOLOGY OF MATERIAL OF PRINCIPLE HYDRAULIC SYSTEMS IN CLASS X TKR VOCATIONAL SCHOOL OF STATE 1 BUNTOK ACADEMIC YEAR 2017/2018 - Bayu Chandra Diputro (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2020)
The purpose of this study was to determine the influence of Talking Stick Learning Model on Student Learning Results in Basic Automotive Technology for Class X TKR Hydraulic System at SMK Negeri 1 Buntok on Academic Year 2017/2018. This research applied the Quasi - Experimental design based on the research design using Nonequivalent Control Group Design. The initial test will be given before treatment while subsequently the final test is afterward. The population for this research is taken from TKR X and X class TSM State Vocational High School or SMK-1 Buntok as many as 56 people students. TKR X class denotes the experimental class with 28 students in which implementing the Talking Stick Learning Model. It is about 34 students used as the control class. The research result shows that the data on student learning outcomes by the Talking Stick learning model provided the average value on 78.64 students. According to the results of t test calculations, we obtained t count > t table, (6.24 > 2.005). However, Ho is rejected and Ha is accepted. This means that the applied learning method such as Talking Stick Learning Model can give the improvement effect on Student Learning Outcomes after implementing the study activity in formal class for Basic Automotive Technology of Hydraulic Systems.